Similar Frequency and Inducibility of Intact Human Immunodeficiency Virus-1 Proviruses in Blood and Lymph Nodes. (3rd December 2020) - Martin, Alyssa R; Bender, Alexandra M; Hackman, Jada; Kwon, Kyungyoon J; Lynch, Briana A; Bruno, Daniel; Martens, Craig; Beg, Subul; Florman, Sander S; Desai, Niraj; Segev, Dorry; Laird, Gregory M; et al.
Abstract: Background: The human immunodeficiency virus (HIV)-1 latent reservoir (LR) in resting CD4 + T cells is a barrier to cure. LR measurements are commonly performed on blood samples and therefore may miss latently infected cells residing in tissues, including lymph nodes. Methods: We determined the frequency of intact HIV-1 proviruses and proviral inducibility in matched peripheral blood (PB) and lymph node (LN) samples from 10 HIV-1-infected patients on antiretroviral therapy (ART) using the intact proviral DNA assay and a novel quantitative viral induction assay. Prominent viral sequences from induced viral RNA were characterized using a next-generation sequencing assay. Results: The frequencies of CD4 + T cells with intact proviruses were not significantly different in PB versus LN (61/10 6 vs 104/10 6 CD4 + cells), and they were substantially lower than frequencies of CD4 + T cells with defective proviruses. The frequencies of CD4 + T cells induced to produce high levels of viral RNA were not significantly different in PB versus LN (4.3/10 6 vs 7.9/10 6 ), but they were 14-fold lower than the frequencies of cells with intact proviruses. Sequencing of HIV-1 RNA from induced proviruses revealed comparable sequences in paired PB and LN samples. Conclusions: These results further support the use of PB as an appropriate proxy for the HIV-1 LR in secondary lymphoid organs. Abstract : This study found that the levels of intact and inducible HIV proviruses found in the blood and the lymph node are similar, and supports the continued use of blood to monitor the status of the HIV latent reservoir.